3-Hydroxybutyrate alleviates septic liver injury by promoting macrophage polarization from M1 to M2 - Hu Jingjuan; Deng Fan; Sun Qishun; Min Yue; Feng Siyuan; Wu Ling; Chen Xiaofeng; Liu Kexuan (生物医学转化)
Objective To investigate the therapeutic effects and underlying mechanisms of the metabolite 3- hydroxybutyrate (3HB) in a cecal ligation and puncture (CLP)-induced sepsis model in mice. Methods Male C57BL / 6J mice were divided into three groups: Sham, CLP, and CLP + 3HB groups. The survival rate, liver histopathological damage, serum levels of Alanine Transaminase(ALT) and Aspartate Aminotransferase(AST), and hepatic mRNA expression of inflammatory cytokines IL-1β and IL-6 were evaluated. Subsequently, macrophages were depleted using clodronate liposomes (Clo-Lipro) to explore their role in 3HB treatment. Male C57BL/6J mice were divided into five groups: CLP, CLP+3HB, CLP+ PBS-Lipro, CLP+Clo-Lipro, and CLP+ 3HB + Clo-Lipro. Peritoneal macrophage polarization (M1 and M2 phenotypes), liver injury, and inflammatory cytokine expression were analyzed. Results Treatment with 3HB significantly improved the survival rate of septic mice, alleviated liver injury, and reduced levels of ALT, AST, IL-1β, and IL-6. 3HB promoted the polarization of macrophages from M1 to the M2 phenotype in septic mice, while macrophage depletion exacerbated liver injury in septic mice and reversed the protective effects of 3HB. Conclusion 3HB alleviates septic liver injury by promoting macrophage polarization from M1 to M2. This effect is dependent on the participation of macrophages, providing new insights and potential intervention strategies for the clinical treatment of septic liver injury.